PENGARUH ENVIRONMENTAL, SOCIAL, DAN GOVERNANCE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Aulia, Siti Nur; Afif, M. Nur; Aziz, Ayi Jamaludin (Jurnal Akuntansi Kompetif, 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosures on the financial performance of energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. Financial performance is measured using the Return on Assets (ROA) indicator, while ESG data is obtained from annual and sustainability reports. The theoretical framework is based on legitimacy theory, stakeholder theory, and signaling theory. Using a quantitative approach and panel data regression analysis through the Random Effect Model, the results show that ESG disclosures—both simultaneously and partially—do not have a significant effect on ROA. The adjusted R-squared value of 1.38% indicates a very low explanatory power of the independent variables in explaining the variation in ROA. These findings suggest that despite the increasing trend in ESG reporting, it has yet to make a substantial impact on short-term profitability in the energy sector. The results imply that ESG implementation must go beyond formal reporting and be substantively integrated into business operations. Investors are also encouraged to continue considering conventional financial indicators when assessing company performance. Future studies are recommended to expand the observation period and include other sectors to obtain more generalizable results. Keywords: Environmental, Social, Governance, Return on Assets, financial performance, energy companies, Indonesia Stock Exchange